Problematika Psikologis Manusia Modern dan Solusinya Perspektif Psikologi dan Tasawuf - Meta Malihatul Maslahat (Syifa al-Qulub, 2021)
Many modern men have lost their way of life and direction because they are too attached to worldly life and forget the metaphysical vision in their lives. Modern man experience many psychological problems because of their inability to balance needs in the bio, psycho, socio and spiritual aspects. Therefore, we need the right solution to reduce the psychological problems that occur in modern man. In this paper, the author wants to examine the psychological problems of modern man and their solutions from the perspective of psychology and Sufism. The method used in this research is a qualitative method using inductive logic. The results of this study indicate that in a psychological perspective the causes of psychological problems in modern man are due to their inability to fulfill the bio, psycho and socio aspects. Meanwhile, in the perspective of Sufism, the factors that cause psychological problems are because of getting away from God. Therefore, the solution for modern man to avoid psychological disorders is by balancing the needs of the bio, psycho, socio, and spiritual aspects. Based on this research, the author also concludes that psychology and Sufism basically do not mutually negate each other but can synergize and complement each other.